Peningkatan Minat Masyarakat Dalam Berinvestasi Sukuk Di Indonesia: Suatu Tinjauan Fenomenologi - Octisa, Meillydia; Ainulyaqin, MH; Achmad, LI; Edy, S (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to analyze people's views on sukuk as an investment instrument, measure Indonesian people's confidence in the halal and safe aspects of sukuk, and identify factors that encourage people to invest in sukuk. The approach used in this research is phenomenology, using in-depth interview techniques with sukuk investors in Indonesia. The results of this research show that there are several factors that encourage Indonesian people's interest in investing in sukuk, such as trust in the halal and safe aspects of sukuk, the desire to make a profit, and the desire to support the sharia economy. The findings of this research contribute to the understanding of the factors that drive Indonesian people's interest in investing in sukuk. These findings can also be used by governments and financial institutions to develop effective strategies to increase public interest in investing in sukuk.